Control of MT1-MMP transport by atypical PKC during breast-cancer progression - Rossé, Carine (2014)
Dissemination of carcinoma cells requires the pericellular degradation of the extracellular matrix, which is mediated by membrane type 1-matrix metalloproteinase (MT1-MMP). In this article, we report a co–up-regulation and colocalization of MT1-MMP and atypical protein kinase C iota (aPKCι) in hormone receptor-negative breast tumors in association with a higher risk of metastasis. Silencing of aPKC in invasive breast-tumor cell lines impaired the delivery of MT1-MMP from late endocytic storage compartments to the surface and inhibited matrix degradation and invasion. We provide evidence that aPKCι, in association with MT1-MMP–containing endosomes, phosphorylates cortactin, which is present in F-actin–rich puncta on MT1-MMP–positive endosomes and regulates cortactin association with the membrane scission protein dynamin-2. Thus, cell line-based observations and clinical data reveal the concerted activity of aPKC, cortactin, and dynamin-2, which control the trafficking of MT1-MMP from late endosome to the plasma membrane and play an important role in the invasive potential of breast-cancer cells. membrane traffic actin cytoskeleton multi-vesicular body MMP14